73‐5: Late‐News Paper: Simplified Implementation of Super Multi‐View Head‐Mounted Display. Issue 1 (29th May 2019) - Takaki, Yasuhiro; Ueno, Takaaki; Yamaguchi, Yuta; Nagahama, Yuki
Abstract : Super multi‐view head‐mounted displays can solve the visual fatigue caused by the vergence–accommodation conflict. This study proposes their simplified implementation, which could greatly reduce the cost and computational load, by using a vibrated flat‐panel display illuminated by LEDs. The experimental validation is also reported.